SAW sensor read range limitations and perspectives - Nawaz, F. (Kluwer Academic Publishers, 2014)
Wireless monitoring systems with passive surface acoustic wave (SAW) sensors offer novel and prodigious perspectives for remote monitoring and control in harsh environments. This paper reviews the working principle of such passive sensors and their state-of-the-art behavior. All major fields of the SAW sensor require operation over a longer reading range, which is the current limitation, hindering the massive implementation of these passive devices. This foremost limitation of the SAW based sensor system occurs when the reply signal strength at the reader becomes too weak for reliable recognition and identification. SAW sensor network read range limitations and advanced techniques for its enhancement are deliberated. Deployment design to maintain the communication reliability and connectivity of the sensor/interrogators network is also discussed. Â© 2014, Springer Science+Business Media New York.